(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Any profession should aim for success and achieving these goals requires dedication. An accomplished person had a happy, balanced existence and, as a result, was well-liked by all. Self-sufficient people or those who look to their family for direction may also struggle with making decisions. But socially imposed gender roles, such the idea that males should support their families while women stay at home, have made it harder for women to juggle work and family obligations. Despite the fact that both genders work comparable hours, women are more likely than men to experience family interference. From this angle to determine the current professional position of female dentists in their practice. Materials and methods: It was a descriptive observational study conducted from July to December 2023. A purposive sampling technique was utilized to collect the data. the total number of respondents were 120. A semi structured pretested questionnaire was given to female dental surgeons who were actively working in the Chattogram city area, visiting various hospitals, clinics, medical colleges and personal private chambers according to inclusion and exclusion criteria. Data was analyzed by using Microsoft excel and SPSS version 25, presented with various tables, graphs and percentages. Results: The findings of the study indicate that the age range of female dentists practicing in different locations is between 24 and 50 years. In addition to their private practice 18% dental surgeons operate in the employment both in government and private sectors, while 75% work exclusively in the private practices. Approximately 91% female dentists are doing only graduation course while PhD and MS are 1% each only. 42% of them have assumed leadership positions at their places of practices, 27% of them are satisfied with their profession as a whole. Conclusion: Presently, there is an upward trend in the quantity of female dentists, the majority of whom are private practitioners due to the scarcity of suitable employment prospects and their desire for flexibility. In academic position the number of female dentists is still very low. Chatt Maa Shi Hosp Med Coll J; Vol.23 (2); July 2024; Page 69-73